Morphological Description and Histological Structure of Kidney in (White Breasted King Fisher) Halcyon Smyrnensis (Linnaeus, 1758) - Isrra Adnan Auda Khadhim (Journal of Global Pharma Technology, 2018)
The result of anatomical examination indicated that the bird of the current study has a pair of kidney that take asymmetrical position on both side of vertebral column in a bony depression called renal fossa within the synsacrum, each kidney composed of three lobes, cranial, middle and caudal lobe, the result of present study indicate that there is a difference in the location of the cranial lobe of left kidney between male and female, whereas the caudal lobe is the largest kidney lobe. The kidney surrounded by a thin capsule of connective tissue, the basic unit of the kidney is the lobule , each lobule consist of cortical and medullary tissue, the lobules looks pear shape and surrounded from two side by interlobular vein and the intralobular vein located in the center of lobule , the kidney consist of two areas cortex and medulla, the cortex occupies more space than the medulla, the cortex contain glomerulus , proximal convoluted tubules and distal convoluted tubule , while the medulla contain thin and thick of Henle,s loop, collecting tubule and collecting duct.Keywords: Kidney, White breasted king fisher, Morphological description, Histological structure.